A Nationwide Analysis of Risk of Prostate Cancer Diagnosis and Mortality following an Initial Negative Transrectal Ultrasound Biopsy with Long-Term Followup. Issue 1 (25th July 2022) - Kawa, Sandra Miriam; Stroomberg, Hein Vincent; Larsen, Signe Benzon; Helgstrand, John Thomas; Toft, Birgitte Grønkær; Vickers, Andrew Julian; Brasso, Klaus; Røder, Martin Andreas
Abstract : Abstract : Purpose: Magnetic resonance imaging (MRI) targeted prostate biopsy has been shown to find many high-grade prostate cancers in men with concurrent negative transrectal ultrasound (TRUS) systematic biopsy. The oncologic risk of such tumors can be explored by looking at long-term outcomes of men with negative TRUS biopsy followed without MRI. The aim was to analyze the mortality after initial and second negative TRUS biopsy. Materials and Methods: All men who underwent initial TRUS biopsies between January 1, 1995 and December 31, 2016 in Denmark were included. A total of 37, 214 men had a negative initial TRUS biopsy and 6, 389 underwent a re-biopsy. Risk of cause-specific mortality was analyzed with competing risks. Diagnosis of Gleason score ≥7 prostate cancer following negative biopsies was analyzed with multivariable logistic regression including time to re-biopsy, prostate specific antigen (PSA), age and digital rectal examination. Results: The 15-year prostate cancer-specific mortality was 1.9% (95% CI: 1.7–2.1). Prostate cancer-specific mortality was 1.3% (95% CI: 0.9–1.6) and 4.6% (95% CI: 3.4–5.8) for men with PSA <10 and >20 ng/ml, respectively. Of the TRUS re-biopsies 12% were Gleason score ≥7 and risk of Gleason score ≥7 increased with longer time to re-biopsy (p <0.001). Mortality after re-biopsy was similar to after initial biopsy. Conclusions: Men with negative TRUS biopsies have a very low prostate cancer-specific mortality, especially with PSA <10 ng/ml. This raises serious questions about the routine use of MRI targeting for initial prostate biopsy and suggests that MRI targeting should only be recommended for men with PSA >10 ng/ml after negative biopsy.